Patronin regulates presynaptic microtubule organization and neuromuscular junction development in Drosophila. - Gao, Z.; Huang, E.; Wang, W.; Xu, L.; Xu, W.; Zheng, T.; Rui, M. (iScience, 2024)
Synapses are fundamental components of the animal nervous system. Synaptic cytoskeleton is essential for maintaining proper neuronal development and wiring. Perturbations in neuronal microtubules (MTs) are correlated with numerous neuropsychiatric disorders. Despite discovering multiple synaptic MT regulators, the importance of MT stability, and particularly the polarity of MT in synaptic function, is still under investigation. Here, we identify Patronin, an MT minus-end-binding protein, for its essential role in presynaptic regulation of MT organization and neuromuscular junction (NMJ) development. Analyses indicate that Patronin regulates synaptic development independent of Klp10A. Subsequent research elucidates that it is short stop (Shot), a member of the Spectraplakin family of large cytoskeletal linker molecules, works synergistically with Patronin to govern NMJ development. We further raise the possibility that normal synaptic MT polarity contributes to proper NMJ morphology. Overall, this study demonstrates an unprecedented role of Patronin, and a potential involvement of MT polarity in synaptic development.